Design of prestressed concrete to AS3600-2009 - Gilbert, R. I.; Mickleborough, N. C.; Ranzi, Gianluca (CRC Press, 2016)
This textbook presents a detailed description and explanation of the behaviour of prestressed concrete members and structures, both at service loads and at ultimate loads, and in doing so, provides a comprehensive and up-to-date guide to structural design.